Графоаналітичний метод пошуку сідлової точки в ігрових задачах інформаційної безпеки - Demchyshyn, M. V.; Levchenko, Ye. G.; Rabchun, D. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2014)
An optimization of resources allocation between information security objects is complicated due to the fact that the opposition occurs in uncertainty conditions when the opponent actions are unknown. First approach to solve this problem is the dynamic re-sources management in which protection reacts to the opponent’s actions effectively by changing the strategy after every opponent’s step. In some cases, the uncertainty causes difficulties in implementing the protection that makes the process of dynamic management impossible. Another approach is based on providing a guaranteed outcome when the allocation of protection resources is not optimal for all strategies of the opponent, but guarantees that, for any of its actions, the information loss will not exceed the defined value. The implementation of this approach is the matrix game saddle point, which reflects the dormancy state of the dynamic confrontation between two sides. The saddle point existence conditions are analyzed in a system of two objects depending on its vulnerability, resources allocation between them, and the conflicting sides resources ratio.